2007
DOI: 10.1128/cvi.00231-06
|View full text |Cite
|
Sign up to set email alerts
|

Use of Serological Assays for Diagnosis of Hepatitis E Virus Genotype 1 and 3 Infections in a Setting of Low Endemicity

Abstract: Because of the occurrence of genotype 3 hepatitis E virus (HEV) in regions of low endemicity, it is important to validate the currently used serological assays for diagnosing infections with viruses belonging to this lineage, since these assays only use antigens derived from genotype 1 and 2 viruses. We evaluated the Genelabs enzyme-linked immunosorbent assay (ELISA) and the RecomBlot from Mikrogen for the detection of HEVspecific immunoglobulin M (IgM) and IgG under conditions of low endemicity. We compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 18 publications
3
82
1
3
Order By: Relevance
“…A serological study showed IgM antibodies to hepatitis E (two assays were used: HEV IgM ELISA by Genelabs, with a sensitivity of 93% and a specificity of 99%; and Recomblot HEV IgM by Mikrogen, with a sensitivity of 85.7% and a specificity of 100% in non endemic regions [5] ). Hepatitis B surface antigen, antibodies to hepatitis C, IgM anti-HAV were absent.…”
Section: Case Reportmentioning
confidence: 99%
“…A serological study showed IgM antibodies to hepatitis E (two assays were used: HEV IgM ELISA by Genelabs, with a sensitivity of 93% and a specificity of 99%; and Recomblot HEV IgM by Mikrogen, with a sensitivity of 85.7% and a specificity of 100% in non endemic regions [5] ). Hepatitis B surface antigen, antibodies to hepatitis C, IgM anti-HAV were absent.…”
Section: Case Reportmentioning
confidence: 99%
“…Various reports indicate that commercial assays sometimes fail to detect specific antibodies in sera from patients with proven HEV genotype 3 infections, and thus the number of autochthonous HEV infections in industrialized regions may have been underestimated [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-reactions among viral hepatitis antibodies have been reported previously. 20 Finally, 1 patient had a result that was either a false positive or the consequence of a technical error; this conclusion is based on the simultaneous negative total HAV antibody and positive IgM antibody results in a more dilute sample. Simultaneous measurement of total antibody and IgM can be performed and may prove to be beneficial in helping physicians correctly interpret HAV serology.…”
Section: False-positive and Low-positive Resultsmentioning
confidence: 98%